2009
DOI: 10.15760/trec.141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Short Duration Unscheduled Absences Among Transit Operators: TriMet Case Study

Abstract: Type of Report and Period Covered Sponsoring Agency Code Supplementary Notes AbstractThis report analyzes factors contributing to short duration (one to three days) unscheduled absences among operators at TriMet, the transit provider for the Portland, Oregon metropolitan region. The analysis draws on a wide array of operator-specific information recovered by transit ITS technologies in combination with information from the agency's human resources, scheduling, incident, and customer relations databases. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…The drivers' average age per garage-day-period decrease the absence by 2.8 drivers for every additional year. However, the average age square term, which is used to understand the non-linear relationship of the variables, indicates a statistically significant positive value, increasing the absence by 0.03 drivers for each additional year, which is consistent with previous research (Strathman et al, 2009a;Strathman, Broach, & Callas, 2009b). Several other personal characteristics-the percentages of female drivers, drivers in the first sixmonths of employment, and drivers with spouse per garage-day-period-seem to increase the total absence, however they were not significant.…”
Section: Multilevel Regression Model 10supporting
confidence: 90%
“…The drivers' average age per garage-day-period decrease the absence by 2.8 drivers for every additional year. However, the average age square term, which is used to understand the non-linear relationship of the variables, indicates a statistically significant positive value, increasing the absence by 0.03 drivers for each additional year, which is consistent with previous research (Strathman et al, 2009a;Strathman, Broach, & Callas, 2009b). Several other personal characteristics-the percentages of female drivers, drivers in the first sixmonths of employment, and drivers with spouse per garage-day-period-seem to increase the total absence, however they were not significant.…”
Section: Multilevel Regression Model 10supporting
confidence: 90%
“…At the system level, the extraboard must be sufficiently staffed to cover open work that, on average, amounts to 16% of TriMet's scheduled service. In this study, statistical analysis of open work patterns found seasonal variability that generally corresponds to the variability of regular operator absences found in previous work (7). Seasonality can be fairly readily accounted for in extraboard work force planning.…”
Section: Discussionsupporting
confidence: 77%
“…This exercise partly depends on determining whether distinct absence patterns exist among regularduty operators. As Strathman et al have shown, operator absence frequencies vary in fairly predictable ways by day of the week, month, year, and garage (7). Apart from absences, open work is directly affected by any work that remains unassigned in quarterly picks and by work that opens up during a quarter due to retirements, quits, and terminations.…”
Section: Factors Affecting Extraboard Performancementioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of factors that complicate open work planning and management. For example, the absence information used in determining the size of the extraboard can be affected by work rules, operator demographics, scheduling practices, or a transit agency's unscheduled overtime work policy (4,5,6,7). The size of the extraboard is also influenced by pay premiums and guarantees, the cost of fringe benefits, and limitations on extraboard managers' ability to combine or break up pieces of open work (8).…”
Section: Introductionmentioning
confidence: 99%